Gonioscopy-assisted Transluminal Trabeculotomy (GATT) in Patients With Secondary Open-Angle Glaucoma Following Vitreoretinal Surgery. Issue 4 (April 2020) - Quan, Ann V.; Yannuzzi, Nicolas A.; Chen, Jenny; Wang, Ye Elaine; Townsend, Justin H.; Chang, Ta Chen
Abstract : Purpose: To examine the short-term efficacy and safety of gonioscopy-assisted transluminal trabeculotomy (GATT) in a series of patients who developed glaucoma following vitreoretinal surgery. Patients and Methods: Retrospective case series of consecutive patients aged above 18 years with secondary open-angle glaucoma following vitreoretinal surgery who had undergone GATT between January 2015 and June 2019. Eyes were excluded if there is<1 month of follow-up or glaucoma before vitreoretinal surgery. Results: Eight eyes of 8 patients were included, with age range 18 to 72 years (median 43.5 y). Mean pretreatment intraocular pressure (IOP) was 32.7±5.1 mm Hg with a mean of 4.8±0.9 medications. Following GATT, mean IOP improved to 13.6±1.8 mm Hg ( P <0.001) with a reduction to 1.6±1.4 medications after a mean follow-up of 8.6 months (range 1 to 25 mo). Five of the 8 eye (62.5%) had silicone oil in the vitreous cavity during GATT, none of which had concurrent oil removal. Conclusions: GATT is a safe and effective procedure for eyes with secondary open-angle glaucoma following vitreoretinal surgery. Further studies are needed to elucidate long-term benefits of angle surgery on eyes with high pressure following vitreoretinal surgery.